MANAGEMENT OF INTERACTION IN THE EDUCATIONAL COMMUNITY NETWORK: Received: 2nd December 2021; Revised: 21st March 2022, 28th March 2022; Accepted: 28th March 2022 - Tkalich, Tatsiana; Gorbachev, Nikolay; Silkovich, Yuri (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The aim of the study is to develop the concept of a knowledge management system that integrates educational content into a single environment of university knowledge using an extensible mathematical model of the subject area of ​​university knowledge in the form of an ontology. The study is being carried out as part of the development of a pilot project on the development of business education at the Institute of Business of the Belarusian State University, and a project in the State Research Program "Methods for updating the content of education based on semantic technologies" (state registration number 20212245). The research methodology is based on the development approaches to modeling knowledge areas of the network educational community of the Institute of Business of Belarusian State University and the ontological model of the subject area of business education. As a result, the architecture of the educational content management system was developed within the framework of the knowledge management system of the university. This proved the effectiveness of online educational communities in business education, a significant increase in the quality of content through the use of a learning content management system.